Selection of Plasmodium falciparum pfcrt and pfmdr1 polymorphisms after treatment with artesunate–amodiaquine fixed dose combination or artemether–lumefantrine in Liberia. (December 2016) - Otienoburu, Sabina; Maïga-Ascofaré, Oumou; Schramm, Birgit; Jullien, Vincent; Jones, Joel; Zolia, Yah; Houzé, Pascal; Ashley, Elizabeth; Kiechel, Jean-René; Guérin, Philippe; Bras, Jacques; Houzé, Sandrine
Abstract Background Plasmodium falciparum uncomplicated malaria can successfully be treated with an artemisinin-based combination therapy (ACT). However resistance is spreading to the different ACT compounds; the artemisinin derivative and the partner drug. Studies ofP. falciparum polymorphisms associated with drug resistance can provide a useful tool to track resistance and guide treatment policy as well as an in-depth understanding of the development and spread of resistance. Methods The role ofP. falciparum molecular markers in selection of reinfections was assessed in an efficacy trial comparing artesunate–amodiaquine fixed-dose combination with artemether–lumefantrine to treat malaria in Nimba County, Liberia 2008–2009.P. falciparum polymorphisms inpfcrt 76, pfmdr1 86, 184 and 1246, andpfmrp1 876 and 1466 were analysed by PCR-RFLP and pyrosequencing. Results High baseline prevalence ofpfmdr1 1246Y was found in Nimba county (38 %).Pfmdr1 1246Y andpfmdr1 86+184+1246 haplotypes NYY and YYY were selected in reinfections in the artesunate–amodiaquine arm andpfcrt K76, pfmdr1 N86 andpfmdr1 haplotype NFD were selected in artemether–lumefantrine reinfections. Parasites harbouringpfmdr1 1246Y could reinfect earlier after treatment with artesunate–amodiaquine and parasites carryingpfmdr1 N86 could reinfect at higher lumefantrine concentrations in patients treated with artemether–lumefantrine. Conclusions Although treatment is highly efficacious, selection of molecular markers in reinfections could indicate a decreased sensitivity or tolerance of parasites to the current treatments and the baseline prevalence of molecular markers should be closely monitored. Since individual drug levels and the day of reinfection were demonstrated to be key determinants for selection of reinfections, this data needs to be collected and taken into account for accurate evaluation of molecular markers for anti-malarial treatments. The protocols for the clinical trial was registered with Current Controlled Trials, under the Identifier Number ISRCTN51688713 on 9 October 2008